Abstinence and alcohol consumption among students 8th grade: the influence of personal, family and sociocultural spheres - Bonito, Jorge (2014)
Introduction: Among the young, the regular or alcohol abuse seems, allying to the individual factors that come together to generate other risk health behaviors, in social environment, including family and school. Currently, alcohol is the most widely consumed psychoactive substance in the world. In the Portuguese case, the Alentejo is the region that registers higher consumption among students. Objectives: This study aimed to know the personal influences of family, group membership and the school environment, on the habits of abstinence and drinking among adolescents from the 8th grade. Methods: We developed a qualitative investigation using the direct method of data collection. The study was conducted in a secondary school with 3rd Cycle of Basic Education of the District of Évora, located in the Central Alentejo, Portugal. Comprehensive semistructured interviews were conducted. The sample consists of ten students, five non-consumer-five consumers, aged between 13 and 15 years old. Results: The trial takes place between 12 and 14 years old as a result of curiosity, explicit or tacit motivation, “styling”, the environment, and the fun of observing behavior. Among the effects of intake indicated as motivators for consumption stands out the reach states of joy and good disposition. Family members tend to encourage moderate drinking on festive occasions. The elements of group membership tend to motivate, explicitly, the intake between pupils consumers. The school promotes initiatives on the theme. Conclusions: The consumption of alcohol among young 8th grade suffers the personal, family and group belonging, despite the legal prohibition of consumption in public spaces and access to the public infuences. The initiatives in school tend to have no effect.